Effects of humidity on the electronic properties of graphene prepared by chemical vapour deposition. (July 2016) - Melios, Christos; Centeno, Alba; Zurutuza, Amaia; Panchal, Vishal; Giusca, Cristina E.; Spencer, Steve; Silva, S. Ravi P.; Kazakova, Olga
Abstract: The effects of humidity on the electronic properties of mono- and bi-layer graphene prepared by chemical vapour deposition and transferred on SiO2 are investigated via simultaneous global transport and local work function measurements using the van der Pauw method and Kelvin probe force microscopy, respectively. It is found that mono-layer graphene on SiO2 is extremely sensitive to water vapour, with water molecules acting as physisorbed loosely bound p-dopants. In the case of a bi-layer stack, produced by double transfer of two graphene layers, the layers are randomly oriented and decoupled with respect to each other. As a consequence, the bottom layer of the bi-layer stack is mostly affected by substrate charges, while the top graphene layer behaves as a decoupled layer, which is externally doped by the water vapour. Moreover, we provide evidence that ambient humidity is only partly responsible for the p-doping of graphene. These findings will assist in the development of reliable graphene-based electronics such as sensors working in ambient air.